Perception on dilapidated building toward the safety of residents and nearby community: case study Waller Court, Ipoh, Perak / Wan Ezmira Farhanah Khairul Fuad - Khairul Fuad, Wan Ezmira Farhanah (2023)
The government has suggested and executed affordable housing initiatives since independence. A house that is affordable is one that can provide the fundamental needs of a citizen. However, low-cost housing is frequently plagued by maintenance issues and ineffective management. Building neglect and dilapidated is a severe issue that must be addressed, as it is a long-term issue that affects both the government and the community. Dilapidated buildings that are no longer maintained by the responsible parties have the potential to endanger the safety of residents and those around them. The aim of this research is to identify the perception on dilapidated building toward the safety of residents and nearby community in Waller Court. This research uses quantitative methodologies for data collection purposes. The research conclusions are the residents' safety has been compromised due to the building's dilapidation, although this differs from the nearby community, which is less affected in terms of safety. The dilapidated of the Waller Court residential building has a significant impact on the residents there and the surrounding neighbourhood, yet the management can do little but continue performing maintenance work if complaints are made.